2017
DOI: 10.1101/151951
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Zika Virus in Salivary Glands of Five Different Species of Wild-Caught Mosquitoes from Mexico

Abstract: 24Zika virus (ZIKV) is a mosquito-borne virus and Aedes agypti has been mentioned as the 25 main vector of the disease. Other mosquito species in the Aedes and Culex genera have 26 been suggested to have the potential for being competent vectors, based on experimental 27 exposition of mosquitoes to an infectious blood meal containing ZIKV. Here, we report 28 the isolation in cell culture of ZIKV from different body parts of wild-caught female 29 mosquitoes (Ae. aegypti, Ae. vexans, Culex quinquefasciatus, Cx. … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…quinquefasciatus for several reasons: (i) they are anthropophilic [26] and ubiquitous in urban areas of Guadeloupe [16], (ii) they are vectors of flaviviruses such as West Nile virus and St-Louis encephalitis virus [17] and (iii) recent scientific literature recognizes Cx. quinquefasciatus as a potential ZIKV vector, based either in vector competence experimental assays and field investigations [5,13,21,22,27]. Three of these studies have even found infectious ZIKV particles in saliva or salivary glands of this mosquito species after artificial infections.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…quinquefasciatus for several reasons: (i) they are anthropophilic [26] and ubiquitous in urban areas of Guadeloupe [16], (ii) they are vectors of flaviviruses such as West Nile virus and St-Louis encephalitis virus [17] and (iii) recent scientific literature recognizes Cx. quinquefasciatus as a potential ZIKV vector, based either in vector competence experimental assays and field investigations [5,13,21,22,27]. Three of these studies have even found infectious ZIKV particles in saliva or salivary glands of this mosquito species after artificial infections.…”
Section: Discussionmentioning
confidence: 99%
“…Even if there is a lack of evidence for natural Cx. quinquefasciatus infections associated with titers compatible with ZIKV transmission [7] the results obtained by several vector competence assays conducted on the species continuously nourish the controversy: the majority of studies showed inability for this species to be infected by ZIKV or detail the impermeability of the salivary gland barrier [19,20], while few reports reveal the presence of infectious ZIKV particles in salivary glands or saliva of this mosquito [21,22]. Therefore, the possibility of Cx.…”
Section: Introductionmentioning
confidence: 99%
“…Considering the results of studies with collected mosquitoes, when the Culex spp. was infected, the Aedes species was infected (30,42,43,45). Only one study (15) presented data that showed neither Culex spp.…”
Section: Discussionmentioning
confidence: 99%
“…tarsalis, and Cx. coronator (Dyar and Knab) (43)(44)(45)(46)(47)(48)(49). Detection of the virus genetic material occurred via real-time polymerase chain reaction (RT-PCR or RT-qPCR), with minimal blood meal titers of 4.0 log 10 PFU/ml and 5.7 plaque-forming unit equivalents per milliliter (3.5 ± 0.1 log 10 ZIKV PFUe/ml titer for freshly fed).…”
Section: Study Selectionmentioning
confidence: 99%
“…Temporary peaks visible in the capture of C. quinquefasciatus (Fig. 1C) show that AGOs can also be effective in surveillance programmes for this insect (Acevedo et al ., 2016) in light of related epidemiological suspicion raised in relation to zika virus transmission (Elizondo‐Quiroga et al ., 2017; Guedes et al ., 2017). However, the abundance of M. domestica and Psychodidae specimens, which was influenced by the type and quantity of attractant used, in addition to the finding that AGOs are effective but not efficient for A. aegypti surveillance, can affect the counting of mosquitoes and occupy space within the capture chamber.…”
Section: Figmentioning
confidence: 99%